Effects of Prostaglandin E(2) and Lipopolysaccharide on Osteoclastogenesis in RAW 264.7 Cells - Kaneko, H. (2007)
INTRODUCTION: Prostaglandins (PGs) can act on both hematopoietic and osteoblastic lineages to enhance osteoclast formation. METHODS: We examined PGE(2) stimulated osteoclastogenesis in RAW 264.7 cells and the role of endogenous PGE(2) in lipopolysaccharide (LPS) stimulated osteoclastogenesis. RESULTS: RANKL (1–100 ng/ml) increased formation of osteoclasts, defined as tartrate resistant acid phosphatase multinucleated cells, with peak effects at 30 ng/ml. Addition of PGE(2) (0.01–1.0 μM) to RANKL (30 ng/ml) dose dependently increased osteoclast number 30 to 150%. Use of NS-398 (0.1 μM) or indomethacin (Indo, 1.0 μM) to block endogenous PG synthesis had little effect on the response to RANKL alone but significantly decreased the response to PGE(2). Addition of LPS (100 ng/ml) to RANKL increased osteoclast number 50%, and this response was significantly decreased by NS-398 and Indo. RANKL and PGE(2) produced small, additive increases in COX-2 mRNA levels, while LPS produced a larger increase. PG release into the medium was not increased by RANKL and PGE(2) but markedly increased by LPS. CONCLUSION: We conclude that RANKL stimulated osteoclastogenesis can be enhanced by PGE(2) and LPS though direct effects on the hematopoietic cell lineage and that these effects may be mediated in part by induction of COX-2 and enhanced intracellular PG production.